Environmental awareness and regulations in banking practices : a case study in Ho Chi Minh city - Dao Hai Yen; Zimmerman, Willi; Nguyen Luong Bach; Truong, Quang; Swedish International Development Cooperation Agency (Sida) (Bangkok : Asian Institute of Technology, 1999)
Industrialization and urbanization though vital for the development of a country, carries heavy environmental impacts, which are not often acknowledged till they reach the level of severity. Vietnam at this stage seems much concerned about the development process with little care for the environment. Careful consideration for the environment would have positive repercussions for the future. Banks have been identified as one of the actors who can play an intermediary role in keeping the balance between the economic activities and conserving the environment. This study aims at finding the banks' interests in supporting environmentally friendly projects and their policy regarding the same. It also investigates the awareness amongst the clients and their desire to implement such projects. The overall analysis has looked into the constraints faced by the government and comes up with proposals for reforms in banking system so that they support environmentally friendly projects. Similarly, an assessment has been made of how banks can get such projects implemented and how awareness amongst the people can be raised to attract them towards such projects. Thus, this study is expected to help in creating a linkage between the policy makers, banks and the clients so that along with economic development and protect environment. Also from this study a new concept of environmental concern has been introduced in the banking system, so that banking system can contribute to environmental protection activities as well as policy maker can use the information from this study for establish environmental policy for banking system. Vietnam can also achieve environmental sustainability in the future.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science. School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1999
Keywords: Banks and banking -- Vietnam -- Ho Chi Minh -- Environmental aspects